2005
DOI: 10.1126/science.1112658
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Seabirds Transport Marine-Derived Contaminants

Abstract: Long-range atmospheric transport of pollutants is generally assumed to be the main vector for arctic contamination, because local pollution sources are rare. We show that arctic seabirds, which occupy high trophic levels in marine food webs, are the dominant vectors for the transport of marine-derived contaminants to coastal ponds. The sediments of ponds most affected by seabirds had 60 times higher DDT, 25 times higher mercury, and 10 times higher hexachlorobenzene concentrations than nearby control sites. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(162 citation statements)
references
References 4 publications
4
157
1
Order By: Relevance
“…This biotic transport of contaminants may be similar in magnitude to atmospheric and oceanic transport (Burek et al, 2008). There is evidence, for example, that Arctic and Antarctic birds may act as vectors transporting persistent contaminants from oceans to terrestrial systems via their guano (Blais et al, 2005). In Canadian coastal ponds under the nesting cliffs of northern fulmars (Fulmarus glacialis), concentrations of HCB, DDT, and mercury were 10 to 60 times higher than contaminant concentrations in sediments from unaffected ponds.…”
Section: Altered Fate and Behavior Of Popsmentioning
confidence: 96%
“…This biotic transport of contaminants may be similar in magnitude to atmospheric and oceanic transport (Burek et al, 2008). There is evidence, for example, that Arctic and Antarctic birds may act as vectors transporting persistent contaminants from oceans to terrestrial systems via their guano (Blais et al, 2005). In Canadian coastal ponds under the nesting cliffs of northern fulmars (Fulmarus glacialis), concentrations of HCB, DDT, and mercury were 10 to 60 times higher than contaminant concentrations in sediments from unaffected ponds.…”
Section: Altered Fate and Behavior Of Popsmentioning
confidence: 96%
“…Our study has shown that seabird colonies, as a consequence of bio-transportation processes, play an important role in increasing the content of and changing the distribution of heavy metals in arctic soils, and that this is a widely described phenomenon (Godzik, 1991;Headley, 1996;Blais et al, 2005;Michelutti et al, 2010;Mallory et al, 2015). This is indicated by the highest scores of Zn, Mn, Cu, and Cd contents in the peat under the avian colony, which is the direct receiver of those inputs (the second point of the transect), and is in agreement with other studies (e.g., Brimble et al, 2009;Michelutti et al, 2009).…”
Section: Discussionmentioning
confidence: 80%
“…The efficiency of pollutant introduction to the terrestrial environment by seabirds is also visible in terms of the heavy metal content in flora. Plants in the proximity of avian colonies show higher concentrations than the same species growing in similar habitats distant from avian colonies (Godzik, 1991;Blais et al, 2005;Evenset, 2007).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations